2001
DOI: 10.1038/sj.bjp.0704127
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation to authentic nitric oxide and SIN‐1 in rat isolated mesenteric arteries: variable role for smooth muscle hyperpolarization

Abstract: 1 Authentic nitric oxide (NO; 0.1 ± 10 mmoles) caused transient, dose-dependent relaxation of phenylephrine-induced tone without changing membrane potential in mesenteric arteries. Larger doses, above 10 mmoles, did not evoke more relaxation (maximal relaxation to 150 mmoles NO in denuded arteries, 69+7%, n=8) but stimulated muscle hyperpolarization (maximum 19+3 mV, n=5). 2 The soluble guanylyl cyclase inhibitor, 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ; 10 mM), abolished relaxation to low doses of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…33 Taken together with our findings, it may be suggested that NO ⅷ and NO Ϫ can mediate vasorelaxation of resistance arteries through distinct mechanisms, namely, the activation of K Ca and K v channels, respectively. These findings are of particular importance in light of the recent reports that the activity of endothelium-derived relaxing factor in large conduit arteries 4,5 more closely resembles the properties of NO Ϫ rather than NO ⅷ .…”
Section: Discussionmentioning
confidence: 77%
“…33 Taken together with our findings, it may be suggested that NO ⅷ and NO Ϫ can mediate vasorelaxation of resistance arteries through distinct mechanisms, namely, the activation of K Ca and K v channels, respectively. These findings are of particular importance in light of the recent reports that the activity of endothelium-derived relaxing factor in large conduit arteries 4,5 more closely resembles the properties of NO Ϫ rather than NO ⅷ .…”
Section: Discussionmentioning
confidence: 77%
“…In arterial smooth muscle, one of the major intracellular facilitators of NO-mediated vasodilation is K ϩ channels (43). In mammalian mesenteric arteries, it has been shown that NO-mediated vasodilation is caused, in part, by opening of Ca 2ϩ -activated K ϩ (K Ca ) (11,30,38,52,62) and voltage-gated K ϩ (K V ) (27,68) channels. In toad, clotrimazole, an inhibitor of large-conductance K Ca (BK Ca ) channels, intermediate-conductance K Ca (IK Ca ) channels, and K V channels (58) significantly decreased the AChinduced vasodilation that is attributed to NO.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have identified an apparent ability of exogenous (18) and endogenous (2) HNO to activate voltage-dependent K ϩ (K v ) channels in the resistance vasculature. In contrast, NO ⅐ targets Ca 2ϩ -activated K ϩ (K Ca ) channels in the same preparation (34). Such distinct actions of these NO redox siblings may facilitate the use of HNO donors over traditional nitrovasodilators for the treatment of vascular dysfunction.…”
mentioning
confidence: 97%